Care packages for your customers : - Glanz, Barbara A. (McGraw-Hill, 2007)
CARE Packages for Your Customers gives you 52 proven, actionable ideas for providing extraordinary service, increasing sales, and ensuring continual business success. By implementing one technique per week, you'll deliver a complete CARE package of exceptional customer service. Providing examples of each technique and tips for successful implementation, this solution-oriented tool also includes